Brainspotting – the efficacy of a new therapy approach for the treatment of Posttraumatic Stress Disorder in comparison to Eye Movement Desensitization and Reprocessing - Anja Hildebrand; David Grand; Mark Stemmler (Mediterranean Journal of Clinical Psychology, 2017)
Objective: This study aims at determining the efficacy of the new therapy approach Brainspotting (BSP) in comparison to the established Eye Movement Desensitization and Reprocessing (EMDR) approach for the treatment of Posttraumatic Stress Disorder (PTSD). Method: The sample consisted of 76 adult seeking professional help after they have been affected by a traumatic event. Clients were either treated with three 60-minute sessions of EMDR (n=23) or BSP (n=53) according to a standard protocol. Primary outcomes assessed were self-reports of the severity of PTSD symptoms. Secondary outcomes included self-reported symptoms of depression and anxiety. Assessments were conducted at pretreatment, posttreatment and 6 month after the treatment. Results: Participants in both conditions showed significant reductions in PTSD symptoms. Effect sizes (Cohen’s d) from baseline to posttreatment concerning PTSD related symptoms were between 1.19 - 1.76 for clients treated with EMDR and 0.74 - 1.04 for clients treated with BSP. Conclusion: Our results indicate that Brainspotting seems to be an effective alternative therapeutic approach for clients who experienced a traumatic event and/or with PTSD.